Task difficulty modulates the effect of mind wandering on phase dynamics - Zhengkun Long; Georg Northoff; Xiaolan Fu (Proceedings of the National Academy of Sciences, 2025)
Mind wandering attenuates widespread sensory and motor processing, both of which are mediated by phase coherence. However, it remains unclear i) whether mind wandering impacts both sensory input and motor output processing by modulating ii) neural entrainment to external stimuli, as measured by intertrial phase coherence (ITPC), and specifically iii) whether task difficulty with different degrees of attentional demands moderates the impact of mind wandering on phase coherence. Using the thought-probe method, we assessed participants’ attentional states during different sensory and motor tasks with varying task difficulty. We found that mind wandering decreased ITPC exclusively in less demanding tasks but not in difficult ones, regardless of whether the tasks involved visual input or motor output processing. Our results suggest that external task difficulty may modulate the balance between external and internal cognitive processing (e.g., mind wandering), with simpler tasks facilitating internally oriented cognition and increasing mind wandering. This balance between internal mind wandering and external task difficulty is mediated, in part, by phase coherence, which serves as an underlying neural mechanism. Collectively, our findings support the hypothesis that phase coherence and its dynamics (ITPC) play a key role in mediating the reciprocal balance of internal and external cognition—this suggests their partly shared cognitive-executive resources as entailed by the recently proposed Baseline model of cognition.